CDH23 Related Hearing Loss: A New Genetic Risk Factor for Semicircular Canal Dehiscence?. Issue 10 (December 2016) - Noonan, Kathryn Y.; Russo, Jack; Shen, Jun; Rehm, Heidi; Halbach, Sara; Hopp, Einar; Noon, Sarah; Hoover, Jacqueline; Eskey, Clifford; Saunders, James E.
Abstract : Objective: To investigate the prevalence and relative risk of semicircular canal dehiscence (SCD) in pediatric patients with CDH23 pathogenic variants (Usher syndrome or non-syndromic deafness) compared with age-matched controls. Study Design: Retrospective cohort study. Setting: Multi-institutional study. Patients: Pediatric patients (ages 0–5 years) were compared based on the presence of biallelic pathogenic variants in CDH23 with pediatric controls who underwent computed tomography (CT) temporal bone scan for alternative purposes. Interventions: Retrospective review of diagnostic high resolution CT temporal bone scans and magnetic resonance imaging (MRI) for evaluation of SCD. Main Outcome Measures: Superior and posterior semicircular canals were evaluated by a neuroradiologist for presence of SCD or abnormal development. Results: Forty-two CT scans were reviewed for SCD. Eighty-six percent of the CDH23 variant group had abnormalities in at least one canal compared with only 12% in age-matched controls. In the CDH23 variant group there were four patients with superior SCD (57%, RR = 10.0) and three patients with posterior canal abnormalities (43%, RR = 7.5) compared with two, and two patients, respectively, in the control population. Four CDH23 variant children had bilateral abnormalities. One child had thinning or dehiscence in both the superior and posterior canals. Relative risk of SCD in children with CDH23 pathogenic variants is 7.5 ( p < 0.001) compared with the pediatric control population. Conclusions: Children with a CDH23 pathogenic variants are at significantly increased risk of having SCD and this may be a contributing factor to the vestibular dysfunction in Usher syndrome type 1D patient population.